Big Data Analytics Capability and Database Integration in Supporting Quality Decision Making in the E-Commerce Industry in Indonesia - Joko Santoso; Anggun Nugroho; Agus Purwanto; Affan Irfan Fauziawan; I Wayan Karang Utama (West Science Information System and Technology, 2026)
The rapid development of Indonesia’s e-commerce industry has increased the importance of data-driven decision-making to improve business competitiveness and operational effectiveness. The availability of massive amounts of digital data requires organizations to develop technological capabilities that enable accurate, timely, and strategic decisions. This study aims to analyze the role of Big Data Analysis and Database Integration in supporting high-quality decision-making within Indonesia’s e-commerce industry. This research employs a quantitative approach involving 105 respondents who are engaged in e-commerce-related activities. Data were collected using a five-point Likert scale questionnaire and analyzed using SPSS version 25 through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, F-test, and coefficient of determination analysis. The results indicate that Big Data Analysis has a positive and significant effect on high-quality decision-making. Database Integration also demonstrates a positive and significant influence on decision-making quality. Furthermore, the simultaneous test confirms that Big Data Analysis and Database Integration significantly affect decision-making quality, with an explanatory power of 62.6% (R² = 0.626). These findings demonstrate that effective utilization of analytical capabilities and integrated database systems enables e-commerce organizations to improve information accuracy, reduce uncertainty, and enhance strategic decision-making processes. This study contributes empirical evidence regarding the importance of digital data capabilities in supporting organizational decision-making within Indonesia’s rapidly evolving e-commerce ecosystem.